Normatividades e instituciones eclesiásticas en el virreinato del Perú, siglos XVI-XIX - Danwerth, Otto; Albani, Benedetta; Duve, Thomas (Global Perspectives on Legal History, 2019)
Ecclesiastical institutions and actors were essential for the formation of normative orders in early modern Ibero-America. In a series of seminars, organised by the Max Planck Institute for European Legal History in Mexico City, Lima, Bogotá and São Paulo, scholars from different disciplines presented innovative studies on the history of religious normativity and its practices. Based upon the Lima colloquium, the present volume focuses on the viceroyalty of Peru (16th-19th centuries).